Efectos del ácido salicílico en la tolerancia de cultivos a factores abióticos de estrés - Burgos Macías, Josué Aljair (2024)
The development of the case study was based on the objective of analyzing the effects of salicylic acid on improving the tolerance of selected crops against abiotic stress factors. For its part, in the methodology process, a basic research with a qualitative approach was established, a bibliographic and descriptive analysis was carried out that was based on analyzing the effects that salicylic acid has on stress processes in plants. In reference to the results, they have been located in the genetic processes in terms of the accumulation of metabolites and in reference to the adaptation and defense response, the relevant changes in the genes linked to the response to stress, these discoveries provide insight most recondite of the biochemical components involved in the resistance of crops to salicylic acid, providing valuable information to optimize their diligence in agricultural practices. In conclusion, this compound triggers a series of biochemical responses in plants that affect their growth and development, salicylic acid induces the synthesis of defense proteins and the activation of antioxidant enzymes, a protective role for plants against biotic and abiotic stress.